Penyuluhan Skrining Anemia dan Pemberian Tablet Fe pada Remaja di SMP 4 Menggala - Yona Desni Sagita; Desma Damita; Sunarsih Sunarsih; Sri Endah Wahyuni; Nawang Sari; Risna Rahayu; Meria Herisa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Anemia is a condition where the hemoglobin level in the blood is less than the normal level. Adolescent girls are at high risk of anemia, because during this period there is an increased need for iron due to growth and mensturation. School activities and high extracurricular activities will have an impact on irregular eating patterns, besides the habit of consuming drinks that inhibit iron absorption will affect one's hemoglobin levels. Adolescent girls are required to take Blood Addition Tablets because they experience menstruation every month. Blood Add Tablet is useful to replace iron lost due to menstruation and to fulfill iron needs that have not been fulfilled from food. Iron in adolescent girls is also useful for improving learning concentration, maintaining fitness and preventing anemia in future mothers. The implementation of this community service activity was held at SMP 4 Tulang Bawang Regency on January 14, 2024. Participants who took part in the education "Counseling on Anemia Screening and Providing Fe Tablets to Adolescents" were 20 junior high school students from SMP 4 menggala. Based on the counseling care carried out, it is known that knowledge about anemia in adolescents, the average knowledge before is 50.5 and after is 87.5, it can be seen that there is an effect of the counseling provided, from counseling it is also seen that the mean difference is 37%. The p-value = 0.000 (p-value < α = 0.05) means that there is an effect of counseling on knowledge about anemia in adolescents.